Ljubljana: City and Myth (L'architettura delle città - The Journal of the Scientific Society Ludovico Quaroni, 2017)
Ljubljana is a city that bears indelible traces of the creativity and originality of one of the great masters of Mitteleuropean modernism, JoÅ¾e PleÄnik; He did not proceed according to an impersonal and universal plan, constructed on paper: the history that interested PleÄnik has a beginning and an end and concerns the people who live in the city. This urban project became a reality through an incessant process of architectural design. Similar to a stage play, the sequence of urban events imagined by the architect, becomes the telling of a story with its own characters and the dialogue between them. Each of the works imagined by PleÄnik appears to refer to a vaster plan for the city. They resemble autonomous parts of a vast urban programme constantly searching for an overall equilibrium. He pursued a precise plan, working with the monumentalisation of the elements that make up public space, constructing a new historic memory for the city.Nonetheless, PleÄnikâ€™s grand scheme was never fully completed, and at the end of his lengthy career as an architect there were more proposals than built works. Beginning in 2004 the city of Ljubljana undertook an ambitious project involving businesses.The project involved the investment of more than 20 million Euro and the construction of a complex programme of interventions involving many young professional offices from the city. Projects were linked, primarily, to the urban infrastructure of the River Ljubljanica, from the city centre to its suburbs.